2006
DOI: 10.1126/science.1123721
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Substrates of Dread

Abstract: Given the choice of waiting for an adverse outcome or getting it over with quickly, many people choose the latter. Theoretical models of decision-making have assumed that this occurs because there is a cost to waiting-i.e., dread. Using functional magnetic resonance imaging, we measured the neural responses to waiting for a cutaneous electric shock. Some individuals dreaded the outcome so much that, when given a choice, they preferred to receive more voltage rather than wait. Even when no decision was required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(238 citation statements)
references
References 30 publications
22
216
0
Order By: Relevance
“…This reflects research finding that people, when given a choice, want to experience unpleasant situations right away, rather than postponing them to later (Berns, Chappelow, Cekic, Zink, Pagnoni, & Martin-Skurski, 2006). Because low response times have been shown in previous studies to be associated with low penalty shot performance (Jordet, in press), one could argue that the behaviours that these players use to respond to the high public team status are self-defeating.…”
Section: Discussionmentioning
confidence: 92%
“…This reflects research finding that people, when given a choice, want to experience unpleasant situations right away, rather than postponing them to later (Berns, Chappelow, Cekic, Zink, Pagnoni, & Martin-Skurski, 2006). Because low response times have been shown in previous studies to be associated with low penalty shot performance (Jordet, in press), one could argue that the behaviours that these players use to respond to the high public team status are self-defeating.…”
Section: Discussionmentioning
confidence: 92%
“…In this chapter, we summarize three neuroeconomic studies previously reported in (Berns et al, 2006;Berns, Capra, Moore, & Noussair, 2007;Berns, Capra, Chappelow, Moore, & Noussair, 2008) and Chandresakhar, Capra, Moore, Noussair, and Berns (2008). There are two features that distinguish these three studies from most others in the experimental economic literature.…”
Section: Introductionmentioning
confidence: 95%
“…The experiment described in this section (see Berns et al, 2006 for more detail) was designed to distinguish between two potential explanations for why observed decisions might be consistent with negative discounting. One possibility is that, in addition to the utility of the outcome, the anticipation of the outcome may yield utility in itself.…”
Section: Why Do People Want To Get An Adverse Experience Over With Asmentioning
confidence: 99%
See 2 more Smart Citations